The effect of sustainable management practices on the bacterial community in different European croplands - Cuartero, J.; Frey, B.; Zornoza, R.; Sánchez-Navarro, V.; Canfora, L.; Özbolat, O.; Egea-Cortines, M.; Farina, R.; Fritze, Hannu; Tuomivirta, Tero; Lång, Kristiina; Lemola, Riitta; et al. (Elsevier, 2025)
Currently, monitoring Europe's soils is crucial since over 60 % of these soils are experiencing different types of degradation, which can potentially affect food production. Recently, a shift toward sustainable soil management has occurred. This shift away from conventional management is postulated to increase soil microbial diversity. However, it is unclear whether sustainable management can shift bacterial community across Europe. The Diverfarming project uses case studies to explore how diversified cropping systems with low-input practices can increase soil fertility, sequester carbon, and increase microbial diversity under differing climate conditions. To explore this, we employed metabarcoding sequencing to amplify the 16S rRNA region and soil chemical properties to assess the effects of organic amendment, rotation/intercropping and diversification with reduced tillage compared to conventional systems in different case studies. We observed that richness and Shannon index were mainly affected by climate and soil chemical properties but not by diversification. However, diversification changed the microbial community and enhanced potential microbial functionality, especially diversification of organic amendments, which also increase total organic carbon and nitrogen. We identified specific bacterial taxa associated with diversification, such as Rubrobacter, MND1, Pontibacter and Sphingomonas, highlighting the potential benefits of some species of these genera in diversification management ecosystems.
Keywords: metabarcoding; soil; sustainable practices; climatic zone; bacteria; PICRUSt